The Arab Republic of Egypt Government’s Policy during Gamal Abdul Naseer Reign (1952-1962) - Ali, Muhammad Nasihudin (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2022)
The focus of this research is concern about Egypt’s policy during the reign of Gamal Abdul Naseer (1952-1962 BC). this research aims to explain 1) Explaining Gamal Abdul Naseer policy in Egpyt. 2) Describing the impact of Gamal Abdul Naseer policy on the development of Egypt. The research choose qualitative method by using descriptive analysis on sociological politic approach as a subject which concentrates on power, government, and authority toward its citizens. The result demonstrated Nasser’s urge in order to improve the politic and economic sector in Egypt during his regime. Nasser initiated a system which supported the growth of political development and fiscal cooperation for improving Egypt as a nation. Nasser started the guided democracy system in Egypt. While in economic sector, Nasser’s goal was to develop industrialization as a solution of Egypt economic problems.